Compressive piezoresistive behavior of carbon nanotube sheets embedded in woven glass fiber reinforced composites. (1st May 2017) - Aly, Karim; Li, Ang; Bradford, Philip D.
Abstract: Due to the difficulties associated with performing compression tests and the complex nature of compression failure, the number of studies that have examined the piezoresistive response of carbon nanotube (CNT) sensing networks in composites under compression loading has been limited. This paper introduces a novel technique for embedding aligned sheets of two millimeter long, interconnected CNTs into the interlaminar region of laminated composite structures to assess the potential of the CNT sheets to function as strain sensing materials for composite structures subjected to axial compression loading. Quasi-static and cyclic compression mechanical loading tests were accompanied by real time electrical resistance change data acquisition and the results suggested that the CNT sheet sensing material composed of six CNT sheets layers exhibited improved sensitivity, stability and repeatability which are vital properties for any successful health monitoring technique. The coupons with six CNT sheets layers embedded exhibited piezoresistivity that showed some linearity in tension and was nonlinear in compression. This piezoresistive response was characterized as anti-symmetric around zero strain all the way until fracture.